Updates on the Prevalence, Quality of Life, and Management of Chronic Cough in Interstitial Lung Diseases - Natalia V. Trushenko; Olga A. Suvorova; Anna E. Schmidt; Svetlana Y. Chikina; Iuliia A. Levina; Baina B. Lavginova; Sergey N. Avdeev (Diagnostics)
Background: Chronic cough is a common symptom in patients with interstitial lung diseases (ILDs), which significantly affects health-related quality of life (HRQoL). The prevalence of chronic cough varies from 30% to almost 90% in different ILDs, with the highest rate in patients with idiopathic pulmonary fibrosis. However, the pathophysiology of cough in ILDs remains poorly understood, with multiple proposed mechanisms contributing to its development. This knowledge gap complicates both clinical assessment and treatment, as current therapeutic strategies target general cough mechanisms rather than ILD-specific pathways. This review synthesizes existing data to clarify distinct cough mechanisms across ILD subtypes and identify opportunities for more targeted therapeutic strategies in this challenging patient population. Moreover, cough can be a clinical marker of disease severity and a predictor of ILD progression and transplant-free survival. Effective cough-specific therapeutic options that consider potential mechanisms, comorbidities, and individual effects on HRQoL are needed for cough associated with ILD. Therefore, the aim of this review was to analyze the prevalence, the impact on HRQoL, the pathophysiology, and the management of chronic cough in ILDs. Methods: We performed a comprehensive search in PubMed, MEDLINE, Embase, and the Cochrane Library. This review included randomized clinical trials, observational studies, systematic reviews, and meta-analyses in adults with chronic cough comparing ILD types. The following were excluded: commentaries, letters, case reports and case series, conference abstracts, and studies and publications lacking cough-specific outcomes. Results: Several approaches to reduce cough frequency and severity were described: antifibrotic agents, neuromodulators, opiates, inhaled local anesthetics, oxygen, speech therapy, and anti-reflux therapy. Some therapeutic approaches, such as oral corticosteroids and thalidomide, can cause significant side effects. Novel agents, such as P2X3 receptor antagonists, which are in phase III trials (COUGH-1/2), show promising results for refractory cough and may benefit ILD-related cough. Conclusions: Thus, a comprehensive assessment of cough is required for effective cough treatment in patients with ILDs considering possible mechanisms and individual impact on QoL.